2006
DOI: 10.1007/s00213-006-0418-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissociation of two behaviors associated with nicotine addiction: Beta-2 containing nicotinic receptors are involved in nicotine reinforcement but not in withdrawal syndrome

Abstract: Taken together, the present data demonstrated a genetic dissociation of two distinct behavioral patterns associated with nicotine addiction. They further suggested that independent molecular mechanisms underlie these two aspects, offering the possibility of controlling them separately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 51 publications
4
54
1
Order By: Relevance
“…Genetic knockout studies have resolved this issue. β2 KO mice showed somatic symptoms, such as excessive rearing, body shakes or over-grooming, during withdrawal precipitated by the broad-spectrum nAChR antagonist mecamylamine (Besson et al, 2006;Salas, Pieri, & De Biasi, 2004). In contrast, β4 KO mice exhibited significantly reduced somatic symptoms during mecamylamine-precipitated withdrawal (Salas et al, 2004), suggesting that somatic symptoms of nicotine withdrawal involve β4-containing but not β2-containing nAChRs.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Genetic knockout studies have resolved this issue. β2 KO mice showed somatic symptoms, such as excessive rearing, body shakes or over-grooming, during withdrawal precipitated by the broad-spectrum nAChR antagonist mecamylamine (Besson et al, 2006;Salas, Pieri, & De Biasi, 2004). In contrast, β4 KO mice exhibited significantly reduced somatic symptoms during mecamylamine-precipitated withdrawal (Salas et al, 2004), suggesting that somatic symptoms of nicotine withdrawal involve β4-containing but not β2-containing nAChRs.…”
Section: Discussionmentioning
confidence: 95%
“…In contrast, the α7 nAChR antagonist MLA had no effect on nicotine CPP or nicotine self-administration (Grottick et al, 2000;Walters et al, 2006but see Markou & Paterson, 2001). Furthermore, β2 KO mice did not self-administer nicotine or develop nicotine CPP, whereas α7 KO mice did develop nicotine CPP (Besson et al, 2006;Picciotto et al, 1998;Walters et al, 2006). Thus, β2-containing nAChRs are involved in many of the effects of nicotine that may contribute to nicotine addiction.…”
Section: Discussionmentioning
confidence: 99%
“…β2 subunit KO mice withdrawn from chronic nicotine do not exhibit withdrawal-associated increases in anxiety, as measured by the elevated plus maze [77]. In contrast, the somatic symptoms of nicotine withdrawal are present in both β2 KO and WT mice, suggesting that the somatic symptoms of nicotine withdrawal are mediated by other nAChR subunits [7,77,146]. Research with other nAChR subunit KO mice has demonstrated that the β4 [146], α5 [77], and α7 nAChR subunits [148] likely mediate the somatic symptoms of withdrawal.…”
Section: The β2 Nachr Subunitmentioning
confidence: 92%
“…In addition, β2-containing nAChRs also mediate several nicotine withdrawal symptoms (see Table 2 for a summary of nAChR subunit KO studies). β2 subunit KO mice do not self-administer nicotine and do not show nicotine-evoked increases in DA release in the ventral striatum, in contrast to WT littermates [7,130]. Similarly, β2 KO mice do not exhibit nicotine CPP, whereas wild-type (WT) mice can learn to associate a previously neutral context with nicotine administration [181].…”
Section: The β2 Nachr Subunitmentioning
confidence: 99%
“…138 Evidence from knockout mice suggests the b 2 -subunit is necessary for nicotine self-administration and thus may be important in nicotine reinforcement. 134,140 Several studies failed to find any associations between genetic variation in CHRNB2, which encodes the b 2 subunit, with smoking initiation or ND. 137,138,141,142 However, Greenbaum et al 139 found that rs2072660, which had been examined in other studies with negative results, and its haplotypes had a nominally significant protective effect against smoking initiation.…”
Section: Cholinergic Receptorsmentioning
confidence: 99%